DIGITALIZATION AND THE DILEMMA OF IMPLEMENTING SAK EMKM: A PHENOMENOLOGICAL STUDY OF COGNITIVE AND SOCIO-TECHNICAL BARRIERS IN MULTISECTOR MSMES IN SERANG CITY - Faishal Rachman Wahid; Masiyah Kholmi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This qualitative phenomenological study examines the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in eight multi-sector MSMEs in Serang City. Through in-depth interviews, participant observation, and document analysis during March-August 2024, it was found that cognitive barriers (misinterpretation of accounting terminology, perceived administrative burden) were the dominant factors hindering the adoption of SAK EMKM. Technical barriers were sector-specific: culinary businesses faced inaccurate recording of daily cash transactions, while photography services businesses experienced difficulties classifying retainer income. This study proposes a "Socio-Cognitive Implementation Barrier" model as an extension of the Technology-Organization-Environment (TOE) framework and recommends an "ESSENTIAL ACCOUNT" program based on the real needs of business actors. The findings contribute to the literature on behavioral accounting and the digital transformation of MSMEs in peri-urban areas of developing countries.